1992
DOI: 10.1111/j.1600-0447.1992.tb03317.x
|View full text |Cite
|
Sign up to set email alerts
|

Disulfiram therapy –adverse drug reactions and interactions

Abstract: Adverse drug reactions (ADR) to disulfiram treatment have been reported as single cases, but few systematic investigations exist. In this study we analysed the spontaneous ADR reports to the Danish Committee on Adverse Drug Reactions during 1968-1991. In that period 154 ADRs to disulfiram were reported, mainly of hepatic, neurological, skin, and psychiatric reactions, in decreasing order of frequency. The safety of disulfiram, estimated on the amount produced and the number of reactions reported, corresponds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 36 publications
(17 reference statements)
1
44
0
1
Order By: Relevance
“…The precise mechanism by which disulfiram produces its neurotoxic side effects is not fully understood. A key role is attributed to the inhibition of dopamine-b-hydroxylase, a copper-containing glycoprotein enzyme that catalyzes the conversion of dopamine to noradrenaline in the catecholamine storage vesicles of peripheral and central adrenergic neurones (Borrett et al 1985;Fisher 1989;Poulsen 1992;Vaccari et al 1996). Disulfiram administration depletes copper ions from many tissues (Marselos et al 1977), an action presumably responsible for the dopamine-b-hydroxylase inhibition in the brain (Goldstein et al 1964;Berger & Weiner 1977).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The precise mechanism by which disulfiram produces its neurotoxic side effects is not fully understood. A key role is attributed to the inhibition of dopamine-b-hydroxylase, a copper-containing glycoprotein enzyme that catalyzes the conversion of dopamine to noradrenaline in the catecholamine storage vesicles of peripheral and central adrenergic neurones (Borrett et al 1985;Fisher 1989;Poulsen 1992;Vaccari et al 1996). Disulfiram administration depletes copper ions from many tissues (Marselos et al 1977), an action presumably responsible for the dopamine-b-hydroxylase inhibition in the brain (Goldstein et al 1964;Berger & Weiner 1977).…”
mentioning
confidence: 99%
“…Maintenance doses range from 125 to 500 mg daily, depending on tolerance to side-effects, which include hepatic, neurological, skin and psychiatric reactions in decreasing order of frequency (Ritchie 1985;Poulsen et al 1992). Neurological complications are usually dose-related and may be reversible if the offending agent is removed early (Mokri et al 1981;Borrett et al 1985;Poulsen et al 1992). The precise mechanism by which disulfiram produces its neurotoxic side effects is not fully understood.…”
mentioning
confidence: 99%
“…En realidad son casos raros e idiosincrásicos probablemente relacionados con una sensibilidad previa al níquel (Berglund, 1995;Brewer y Hardt, 1999). Generalmente se produce un caso sobre 25.000 pacientes al año (Poulsen, 1992) y la recuperación es automática si se deja de suministrar disulfiram ante los primeros síntomas. Los casos de muerte por una reacción de disulfiramalcohol también son extremadamente raros (Chick y Brewer, 1999).…”
Section: Si Es Tan Bueno ¿Pórque No Se Utiliza Más?unclassified
“…It is rare and idiosyncratic and probably related to previous nickel sensitisation (Berglund 1995;Brewer & Hardt 1999). There is about one case in 25,000 patient years (Poulsen, 1992) and if disulfiram is stopped at the first signs, recovery is invariable. Death from the disulfiramalcohol reaction also seems to be extremely rare.…”
Section: If It's So Good Why Isn't It Used More?mentioning
confidence: 99%
“…Disulfiram toxicity may present different clinical aspects : (1) Cytolytic hepatitis with fatal ovulation in 30% of cases (fulminant hepatitis). Enghusen et al (1992) in their study of Adverse Drug Reaction (ADR) to disulfiram treatment have reported 1 per 2000 treatment year mainly of hepatic neurological, skin and psychiatric reaction in decreasing order of frequency and death 1 per 25000 treatment year [3]. Reports to the WHO collaborating center for Industrial Drug monitoring in Upp sala, Sweden, showed the same ADR profile, although with a higher rate of neurological and psychiatric and a lower rate of hepatic reaction, The latency time from the start of treatment tv the rma.fc-ration of the ADR differe.l according to organ.…”
mentioning
confidence: 99%